Payments for Environmental Services in Costa Rica - Pagiola, Stefano (2012)
Costa Rica pioneered the use of the payments for environmental services (PES) approach in developing countries by establishing a formal, country-wide program of payments, the PSA program. The PSA program has worked hard to develop mechanisms to charge the users of environmental services for the services they receive. It has made substantial progress in charging water users, and more limited progress in charging biodiversity and carbon sequestration users. Because of the way it makes payments to service providers (using approaches largely inherited from earlier programs), however, the PSA program has considerable room for improvement in the efficiency with which it generates environmental services. With experience, many of these weaknesses are being gradually corrected as the PSA program evolves towards a much more targeted and differentiated program. An important lesson is the need to be flexible and to adapt to lessons learned and to changing circumstances.